SALBUTAMOL: A SUBSTITUENT OF ISOPROTERENOL TO ESTABLISH AN EXPERIMENTAL ANIMAL MODEL TO INDUCE MYOCARDIAL INFARCTION - N. Afsheen; Khalil-ur-Rehman; N. Jahan; K. M. Khan; M. A. Zia (Journal of Animal and Plant Sciences, 2017)
Isoproterenol, a catecholamine acting as a β adrenergic agonist, is commonly used to establish myocardial infarction (MI) in animal models for drug development. Although cheaper than isoproterenol, salbutamol is another type of catecholamine, may be potentially and equally used for the onset of MI in animal model. However the concentrations of salbutamol for inducing MI need to be optimized and standardized. In current work, following the treatment with different concentrations of salbutamol, the blood samples of rats were taken at different time intervals according to “Central Composite Design” (CCD) for measuring the level of cardiac markers, CK-MB, LDH and SGOT. Response Surface Methodology (RSM) indicated an optimal salbutamol dosage of 80 mg/kg for inducing MI, which resulted in elevated level of SGOT after 20 hr with CK-MB and LDH level changes in 23 hr following salbutamol (80 mg/kg) administration. The level changes of cardiac marker Trop I and ECG also confirmed the onset of myocardial infarction at the optimal concentration of salbutamol. Current work obtained the optimal dose and the feasibility of salbutamol as a substituent of isoproterenol for inducing MI.
Keywords: Salbutamol; CCD; MI; RSM